2017
DOI: 10.1039/c7dt01077j
|View full text |Cite
|
Sign up to set email alerts
|

From polyethylene waxes to HDPE using an α,α′-bis(arylimino)-2,3:5,6-bis(pentamethylene)pyridyl-chromium(iii) chloride pre-catalyst in ethylene polymerisation

Abstract: Five examples of α,α'-bis(arylimino)-2,3:5,6-bis(pentamethylene)pyridyl-chromium(iii) chlorides (aryl = 2,6-MePh Cr1, 2,6-EtPh Cr2, 2,6-i-PrPh Cr3, 2,4,6-MePh Cr4, 2,6-Et-4-MePh Cr5) have been synthesized by the one-pot template reaction of α,α'-dioxo-2,3:5,6-bis(pentamethylene)pyridine, CrCl·6HO and the corresponding aniline. The molecular structures of Cr1 and Cr4 reveal distorted octahedral geometries with the N,N,N-ligand adopting a mer-configuration. On activation with an aluminium alkyl co-catalyst, Cr1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 61 publications
9
54
0
Order By: Relevance
“…Despite using MMAO as the activator, there are, as with MAO, just two types of end‐group combinations (i.e., vinyl/methyl and methyl/methyl); no evidence for any isopropyl groups could be found in the high‐temperature 13 C NMR spectrum. This absence of isopropyl groups has previously been noted with other MMAO‐promoted chromium catalysts, and can be attributed to the active species displaying a preference to transfer the higher‐concentration methylaluminum.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Despite using MMAO as the activator, there are, as with MAO, just two types of end‐group combinations (i.e., vinyl/methyl and methyl/methyl); no evidence for any isopropyl groups could be found in the high‐temperature 13 C NMR spectrum. This absence of isopropyl groups has previously been noted with other MMAO‐promoted chromium catalysts, and can be attributed to the active species displaying a preference to transfer the higher‐concentration methylaluminum.…”
Section: Resultssupporting
confidence: 69%
“…On the other hand, the Cr2 /MMAO system shows higher activities at 20 or 30 °C, and the polymers exhibit lower melting temperatures as well as narrower molecular weight distributions. As with the MAO‐promoted system, short run times lead to increased activity with a maximum of 15.96 × 10 6 g (PE) · mol –1 (Cr) · h –1 reached after 5 min (Entry 13, Table ), and these findings are consistent with rapid formation of the active species followed by gradual deactivation on prolonging the reaction time , , …”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…δ 1.41; 13 C ca . δ 30.0) with chemical shifts that are characteristic of linear polyethylene; Figures and show the corresponding spectra of the polyethylene obtained using Co1 /MAO (entry 1, Table ) while those obtained using Co1 /MMAO are given in Figures S5 and S6 (entry 1, Table ) . In addition, no evidence for signals corresponding to saturated or unsaturated end groups could be detected which further highlights the high molecular weight of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various catalytic systems available, chromium complexes bearing anionic and neutral polydentate Schiff base ligands have been utilized in oligomerization and polymerization of ethylene due to their advantages of easy preparation and tunable steric and electronic properties . For instance, a detailed study developed by Gibson and co‐workers based on Cr(III) complexes incorporating bidentate and tridentate Schiff base salicylaldimine ligands showed that the catalytic performances of these precatalysts (oligomerization versus polymerization behavior) are strongly influenced by the nature of the groups at the imine nitrogen donor .…”
Section: Introductionmentioning
confidence: 99%